Modeling the slag flow and heat transfer with the effect of fluid-solid slag layer interface viscosity in an entrained flow gasifier. (25th July 2017) - Zhang, Binbin; Shen, Zhongjie; Liang, Qinfeng; Xu, Jianliang; Liu, Haifeng
Highlights: Modeling the slag layer characteristics with the effect of fluid-solid slag layer interface viscosity. The smoother the viscosity-temperature profile, the higher the effects of the fluid-solid slag interface viscosity. The critical viscosity can be regarded as the fluid-solid interface viscosity for the crystalline slag. Abstract: The characteristics of slag flow and heat transfer in a gasifier are significant for controlling the operation conditions. Determination of the fluid-solid slag layer interface is a crucial procedure in the studying of slag flow and heat transfer characteristics. The varied absolute viscosities were used as the fluid-solid slag layer interface viscosity to model the slag layer properties in an entrained flow gasifier. The results showed that with the increase of fluid-solid slag layer interface viscosity, the liquid slag layer thickness increased, while the solid slag layer thickness and the liquid slag velocity decreased. Moreover, the slag layer overall thickness had a slight decrease, while the slag heat flux had a slight increase. In addition, the effects of the fluid-solid slag layer interface viscosity on slag layer characteristics with glassy slag and plastic slag were relatively higher than crystalline slag. The smoother the viscosity-temperature profile, the higher the influences of the fluid-solid slag layers interface viscosity. The critical viscosity could be approximate regarded as the fluid-solid slag layer interface viscosity when the slag type was crystalline slag during the model derivation, and the fluid-solid interface viscosity can be defined as about 100 Pa s for plastic slag and glassy slag.